The Application of the Perma Model in Mental Health Education in Colleges and Universities - Cheng, Chen; Lan, Li (Informatica, 2024)
Accelerated technological development has an impact on how people live. Nowadays, several issues limit the amount of mental health education offered at colleges (e.g. the complex mentality of college students). The orderly growth of culture and traditions education and mental health education programs in colleges and universities may play a significant role in maximizing the dissemination of cultural and ideological notions and modifying the psychological condition of university students. The conventional education and mental health teaching work at universities has been deeply impacted and transformed due to the progressive advancement of data transmission and distribution innovation, which has had a very substantial and far-reaching effect. This research builds a PERMA model of mental health education (MHE) methodologies and focuses mostly on the mental health education of university students. In this approach, “Positive emotion, Engagement, Relationships, Meaning, and Achievements” are used to describe health. Initially, the issues with college students’ mental health education were listed, and an expansion model for mental health education in institutions was developed. The PERMA techniques for college MHE were developed based on this. Secondly, to efficiently choose and optimize the extendable techniques, a performance evaluation model was proposed. This study’s findings support the application of mental health theory to the setting of college students and give a deeper knowledge of the aspects of health education in this demographic. Finally, our accuracy forecast for proposed approaches was 93%.